Aerotoxic Syndrome—Susceptibility and Recovery - Jeremy J. Ramsden (Toxics, 2025)
Significant numbers of aircrew and jet airline passengers are affected by post-flight symptoms of ill health, usually nowadays labelled “aerotoxic syndrome”. It could be inferred from a large passenger survey carried out in the Netherlands that up to 50% of flights may engender malaise to varying degrees, and up to 50% of the population might be susceptible to suffering from actual intoxication from the contaminants known to occur in aircraft cabin air. In-flight measurements of its composition have revealed the presence of known neurotoxins, notably tricresyl phosphate and carbon monoxide, both of which can enter the cabin air as it is bled off the main engines. This study reviews the quantitative aspects of this evidence and estimates the susceptibility of the population to neurological damage at the measured levels of contamination, its typical impacts on health, and the likelihood and timescales of post-exposure recovery. Airworthiness directives already mandate that crew and passenger compartment air must be free from harmful or hazardous vapours and gases, but uncertainty regarding the nature of these particular hazards has led to this important aspect of airworthiness having been hitherto unduly neglected. The continuing exponential growth of air passenger traffic means that cabin air contamination will eventually become a major public health hazard if effective action is not taken, some possible courses of which are discussed.